Tremor Analysis Using Surface Electromyography: Is It Required? - Akıncı, Tuba; Başçı, Nur; Gündüz, Ayşegül; Kızıltan, Meral E. (Cerrahpaşa Medical Journal, 2024)
Objective: In this study, we aimed to compare the role of clinical examination and the contribution of surface electromyography in a population of patients with tremor. Methods: We retrospectively evaluated the medical records of patients who underwent surface electromyography with a preliminary diagnosis of tremor between 2010 and 2022. We retrieved the demographic data and referring specialty (general neurology, movement disorder specialist, nonneurology department) from records. We reclassified phenomenology and underlying etiology according to the latest revision of the Movement Disorders Society classification. We re-evaluated the findings in surface electromyography. Results: Based on clinical examination, 130 patients (63 women, aged 6-82 years, mean age: 39.7 years) had the phenomenological diagnosis of tremor. Surface electromyography changed the tremor diagnosis in 67 (51.5%) of the patients. The diagnoses of essential tremor, epilepsy, and antiseizure medication-induced tremor, tremor related to metabolic disease, and drug-induced tremor were changed in 3 patients, 6 patients, 5 patients, and 1 patient, respectively. The discrepancy between clinical and surface electromyography was seen in 11.5% of the cases. This discrepancy was infrequent among movement disorder specialists (20%) compared to non-neurology branches (40%) and general neurology (40%) (P = .007). Conclusion: As seen in our study, tremor and myoclonus may have similar clinical features in some cases, especially for relatively inexperienced clinicians. Surface electromyography provides the differential diagnosis of tremor and myoclonus. Surface electromyography may be recommended to distinguish between tremor and myoclonus, to identify specific tremor subtypes such as functional tremor, and to identify myoclonus subtypes. Cite this article as: Akıncı T, Başçı N, Gündüz A, Kızıltan ME. Tremor analysis using surface electromyography: is it required? Cerrahpaşa Med J. 2024;48(3):272-274.